2007
DOI: 10.1089/thy.2006.0306
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte and Immature Dendritic Cell Infiltrates in Differentiated, Poorly Differentiated, and Undifferentiated Thyroid Carcinoma

Abstract: Though a relationship between the extent of lymphocyte/DC infiltrates and the prognosis of PTCs could not be demonstrated, tumors with poor prognosis (PDCs, UCs) were characterized by markedly reduced lymphocyte/DC infiltrates. The study appears to confirm the protective role of DC and infiltrating lymphocytes against thyroid tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(77 citation statements)
references
References 17 publications
4
68
0
1
Order By: Relevance
“…75 In contrast, a reduced or absent DC infiltration in PDTC and ATC was described in comparison to DTC. 76 TAMCs: Tumor-associated mast cells…”
Section: Dendritic Cells (Dcs)mentioning
confidence: 99%
“…75 In contrast, a reduced or absent DC infiltration in PDTC and ATC was described in comparison to DTC. 76 TAMCs: Tumor-associated mast cells…”
Section: Dendritic Cells (Dcs)mentioning
confidence: 99%
“…For instance, high T-regulatory cell density correlates with thyroid cancer aggressiveness, and an increased number of immunoregulatory natural killer cells has been demonstrated in PTC compared to normal tissues [39,40]. Furthermore, is has been shown that the degree of lymphocyte and immature dendritic cell infiltration correlated with better prognosis in PTC [41,42], whereas increased macrophage density in poorly differentiated thyroid carcinoma correlated with invasive features and worsened prognosis [43]. Jung et al found that tumor-associated macrophage density correlated with more aggressive subtypes, like anaplastic thyroid carcinoma [44].…”
Section: Tumor Metabolism and The Microenvironment In Thyroid Cancermentioning
confidence: 99%
“…DCs have also been proposed to participate in the development of thyroid cancer. In PTC rich DCs infiltrates were reported in all different histotypes [26]. DCs present a precise distribution in tumors; immature DCs are generally located within PTC nodules, while mature DCs are observed around tumor [31,34].…”
Section: Dendritic Cells (Dcs)mentioning
confidence: 97%
“…Nevertheless, higher prevalence of multifocal or bilateral lesions was reported in TC patients with coexisting CLTI [24] and recently Iliadou el al [25] showed that children and adolescents with CLTI presented more frequently familial PTC, even if no differences in outcome were found with respect to the presence of CLTI. In this regard, it should finally be noted that TC histotypes with a worse prognosis (PDTC, ATC) are characterized by a very reduced lymphocyte infiltration [26].…”
Section: Thyroid Cancer and Autoimmunity: Epidemiological And Clinicamentioning
confidence: 99%